2017
DOI: 10.1002/prp2.374
|View full text |Cite
|
Sign up to set email alerts
|

Distortion of KB estimates of endothelin‐1 ETA and ETB receptor antagonists in pulmonary arteries: Possible role of an endothelin‐1 clearance mechanism

Abstract: Dual endothelin ETA and ETB receptor antagonists are approved therapy for pulmonary artery hypertension (PAH). We hypothesized that ETB receptor‐mediated clearance of endothelin‐1 at specific vascular sites may compromise this targeted therapy. Concentration‐response curves (CRC) to endothelin‐1 or the ETB agonist sarafotoxin S6c were constructed, with endothelin receptor antagonists, in various rat and mouse isolated arteries using wire myography or in rat isolated trachea. In rat small mesenteric arteries, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…On the other hand, the selective ETA receptor antagonist (BQ123) only statistically increased ET-1 levels in HPA, this unexpected result and a role in clearance for ETA should be confirmed (Figure 3). Our results may not only involve endothelial cells but also other cells present in the lung preparations, and a previous study suggested that ET-1 clearance occurs in both endothelial cells and hPASMCs 53 . Several studies have shown elevated levels of ET-1 in plasma and HPA derived from PH Group-III patients 13-15, 54 .…”
Section: Even Though We Have Demonstrated a Higher Eta/etb Receptor Esupporting
confidence: 63%
“…On the other hand, the selective ETA receptor antagonist (BQ123) only statistically increased ET-1 levels in HPA, this unexpected result and a role in clearance for ETA should be confirmed (Figure 3). Our results may not only involve endothelial cells but also other cells present in the lung preparations, and a previous study suggested that ET-1 clearance occurs in both endothelial cells and hPASMCs 53 . Several studies have shown elevated levels of ET-1 in plasma and HPA derived from PH Group-III patients 13-15, 54 .…”
Section: Even Though We Have Demonstrated a Higher Eta/etb Receptor Esupporting
confidence: 63%
“…The protocol of using only a single concentration of each venom was chosen due to rapid desensitization in vascular relaxation responses observed with various Australian elapid snake venoms ( Chaisakul et al, 2012 ; Chaisakul et al, 2013 ; Chaisakul et al, 2014 ). In a separate set of experiments, P. textilis venom (30 µg/ml) was tested after pretreatment (30 min; literature supporting each chosen antagonist concentration shown) with one of 1) the CGRP antagonist CGRP 8–37 (3 µM) ( Wisskirchen et al, 1998 ); 2) the cyclooxygenase inhibitor indomethacin (3 µM) ( Kassab et al, 2017 ); or 3) the nitric oxide synthase inhibitor L-NAME (100 µM) ( Angus et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%